Pengembangan Media Pembelajaran Interaktif Berbasis Android Untuk Pembelajaran Terbuka dan Jarak Jauh di Universitas Pendidikan Indonesia - Firmansyah, Feri Hidayatullah; Sari, Intan Permata; Musyarofah, Musyarofah (Universitas Pendidikan Indonesia (UPI), 2019)
This research aims to develop a learning media as a pilot project for the development of open and distance learning. Learning media developed in the form of android-based applications with project-based learning methods. Media is made by adjusting the objectives of the learning process, therefore the media must have a reference to develop the content of the material to be discussed in it. Content includes RPS, learning modules and assessment grids. Learning media created based on google so that it supports all types of devices to access this module. With the Rapid Application Development (RAD) method the module development stages can be completed in accordance with the planned time. In the module developed there are learning objectives, practical activities instructions, tools and materials, basic theories, exercises and assignments. The material is also given a video sample of the material being studied. The current research has reached the stage of questionnaire filling by students and questionnaire data processing. The results showed a positive response from students evidenced by the normal curve of the assessment that has been carried out. From the data obtained can be used as a reference in the development of interactive learning media that are easy to develop in learning.